(3GYeGd GdGYdGes - (3eMeO Hf YHO Gddg Hf SYjO GdSdeGfj GddhTj GdCUd, GdZQfGWj GdCfOdSj, CHh YHO Gddg, GdTgjQ HdSGf GdOjf GHf GdNWjH,J (B776 (3g` s
(3ChdgG (B:s
(3Chd GdehLhO efg (B: (3aUd ai dWGFa Gddg JYGdi Cf Yde HGdbde Yde GdEfSGf eG de jYde s
(3BNQgG (B:s
(3jfJgi CKfGA GdcdGe Yf OhdI GdCejQ YHO GdeDef Hf Ydi Chd GdehMOjf s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B235s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
(3GdfSNI fGbUI GdChd , eHJhQI GdBNQ s
Keywords: (3GdJGQjNs